Thermodynamic design optimisation of an open recuperative twin-shaft solar thermal Brayton cycle with combined or exclusive reheating and intercooling - Meas, Matthew Robert (Department of Mechanical Engineering, 2017)
The Gouy-Stodola Theorem implies that the net power output of a system can be maximised by synchronously sizing the components, thus minimising the cumulative entropy generation rate. The resulting optimal design is related to, and therefore characteristic of, the cycle configuration, since the entropy generation rates in the individual components are interdependent. In this work, optimal design of three common open solar thermal Brayton cycle variants is investigated and compared using principles of the second law of thermodynamics and the method of entropy generation minimisation. The basic cycle, modified accordingly to construct the reheated, intercooled and combined cases, comprises a modified cavity receiver, a counter-flow plate-type recuperator, and a pair of proprietary automotive turbochargers configured to operate as micro-turbines. An additional modified cavity receiver and cross-flow plate heat exchanger constitute the reheater and intercooler, respectively. Net power output is expressed in terms of the temperature and pressure fields in each case, defined in terms of geometric variables characteristic of the components. Heat addition is calculated using the receiver sizing algorithm developed by Stine and Harrigan. Maximum constraints are applied to the recuperator and intercooler lengths and to the surface temperatures of the receiver and reheater absorber tubes. The dynamic-trajectory method is implemented to optimise the variables such that the net power output is maximised. An array of inputs are considered and compared, including 22 micro-turbine models, eight concentrator diameters ranging from six to 20 meters, and both circular and rectangular absorber tube profiles. The influence of receiver inclination, concentrator optics, environmental conditions and design constraints are investigated and the optimisation subroutines validated in the Flownex simulation environment. Results show the optimised power output, operating conditions and design parameters. The intercooled case demonstrates both the highest ratio of total irreversibility to heat input and the highest power output per unit collector surface area. The combined and reheated cases follow. Temperature differences across the components are identified as the primary cause of entropy generation. The optimised heat exchanger lengths are shown to lie on their maximum constraints, and the channel cross-sections found to decrease in size with increasing mass flow rate such that the heat transfer area is maximised and the heat transfer effectiveness improved. As such, plate counts in the optimised heat exchangers are found to be relatively high, and investigation of various compact heat exchanger designs, and regenerative- as opposed to recuperative heat exchangers, is recommended for future work on this topic. The receiver and reheater geometric parameters are found to change such that the absorber tube surface temperatures are kept below the maximum constraint. Trends in the data obtained for circular section absorber tubes are found to be less smooth than the trends in the data obtained for absorber tubes of rectangular section, indicating that the geometric constraints required to maintain the receiver shape offer greater design flexibility for rectangular section absorber tubes than for absorber tubes of circular section. It is concluded that the increases in the compressor and turbine outlet temperatures with mass flow rate and compressor pressure ratio drive the changes in the temperature differences across the heat exchangers, and thus the component entropy generation rates. The entropy generation rates must in turn be distributed during the optimisation procedure such that the cumulative rate is less than the power output, and all of the constraints are met.